2023
DOI: 10.1111/sms.14410
|View full text |Cite
|
Sign up to set email alerts
|

A scalable school‐based intervention to increase early adolescents' motor competence and health‐related fitness

Abstract: Schools are key settings for the promotion of students' physical activity, fitness, and motor competence. The purpose of our study was to investigate the efficacy of a 5‐month‐long intervention program that aimed to increase students' motor competence and health‐related fitness during school days. We conducted a quasi‐experimental study with 325 Finnish Grade 5 (Mage = 11.26, SD = 0.33) students from five schools. Two schools were allocated to the intervention group and three schools to the control group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The cardiorespiratory response to HIIT has attracted intense attention among researchers. We used 20-m SRT to estimate the VO 2max as previous studies suggested ( Huhtiniemi et al, 2023 ; Luo et al, 2023 ). We found a significant increase in VO 2max among subjects after two regimes of HIIT, which is unsurprising, as previous studies have shown that HIIT based on running or cycling can significantly increase VO 2max ( Batacan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiorespiratory response to HIIT has attracted intense attention among researchers. We used 20-m SRT to estimate the VO 2max as previous studies suggested ( Huhtiniemi et al, 2023 ; Luo et al, 2023 ). We found a significant increase in VO 2max among subjects after two regimes of HIIT, which is unsurprising, as previous studies have shown that HIIT based on running or cycling can significantly increase VO 2max ( Batacan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiorespiratory fitness (CRF) and maximal aerobic speed (MAS) were measured by a multistage 20-m shuttle run test (20-m SRT). The 20-m SRT is widely used to test the cardiorespiratory fitness and has been validated as a reliable predictor of maximum oxygen uptake (VO 2max ) ( Leger and Lambert, 1982 ; Huhtiniemi et al, 2023 ; Luo et al, 2023 ). Compared to traditional methods of assessing VO 2max, the 20-m SRT is simple, easy to administer and not too time-consuming, it requires minimal equipment, and a large number of individuals can be tested simultaneously ( Mayorga-Vega et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, the situation can still be improved. Huhtiniemi and colleagues (2023) have shown that if physical fitness exercises are consistently integrated into school programs, all indicators of health-related physical fitness improve [ 8 ]. And, of course, regular weekly exercise helps to increase the level of physical fitness, especially just muscle strength and cardiorespiratory endurance [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that to improve physical fitness, children aged 5–17 must engage in moderate to vigorous physical activities, as recommended by the WHO [ 5 ]. Both regular weekly training [ 6 , 7 ] and short, intense exercises during school [ 8 ] contribute to the development of strength and endurance.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The study by Grendstad and Hallen also suggests that focusing on other type of training does not either compromise the development of VO 2max if the main interest is in the endurance sports. Higher intensity training is often required for further development when fitness is high but concentrating more on "low hanging fruits" such as general active lifestyle and training various (motor) skills, technique, speed, agility, jumps, strength, balance, and coordination might develop more balanced and prepared body 4,5 for development and harder training later in adolescence and adulthood. This might also better reduce sports-related problems in youth such as overuse injuries 6,7 when training is not monotonic and too intensive.…”
mentioning
confidence: 99%